Long-Term Sustainability of Functional Improvement Following Central Corpectomy for Cervical Spondylotic Myelopathy and Ossification of Posterior Longitudinal Ligament. Issue 12 (15th June 2018) - Sarkar, Sauradeep; Rajshekhar, Vedantam
Abstract : Study Design: Retrospective study. Objective: To examine predictors of long-term outcome and sustainability of initial functional improvement in patients undergoing corpectomy for cervical spondylotic myelopathy (CSM) or ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: There are limited data on the predictors of outcome and sustainability of initial functional improvement on long-term follow-up after cervical corpectomy. Methods: We studied the functional outcome at more than 1-year follow-up after central corpectomy in 352 patients with CSM or OPLL. Functional status was evaluated with the Nurick grading system. Analysis was directed at identifying factors associated with both improvement in functional status and the achievement of a "cure" (improvement to a follow-up Nurick grade of 0 or 1). A survival analysis was performed to identify factors associated with sustained functional improvement in patients with serial follow-up evaluations. Results: Nurick grade improved from 3.2 ± 0.1 to 1.9 ± 0.1 over a mean follow-up period of 57.1 months (range 12–228 mo). On multivariate analysis, age ≥50 years ( P  = 0.008) and symptom duration ≥1 year ( P  < 0.001) were negatively associated with functional improvement by ≥1 Nurick grade. Independent factors negatively associated with "cure" after surgery included age 50 years or older ( P  = 0.005), preoperative Nurick grade of 4 or higher ( P  < 0.001) and symptom duration of 1 or more years ( P  < 0.001). Early improvement in functional status was maintained in 90.5% and 76.3% of patients at 5 and 10 years follow-up, respectively. On survival analysis, patients with shorter preoperative symptom duration (<1 yr) were more likely to demonstrate sustained improvement in functional status after surgery ( P  = 0.022). Conclusion: Initial gains in functional status after central corpectomy for CSM and OPLL are maintained in more than 75% of patients at 10 years after surgery. Overall, the most favorable long-term outcomes are achieved in younger patients who present early and with good preoperative functional status. Level of Evidence: 4